Inactivation of Gram-Negative Bacteria by Lysozyme, Denatured Lysozyme, and Lysozyme-Derived Peptides under High Hydrostatic Pressure - Masschalck, Barbara (American Society for Microbiology, 2001)
We have studied the inactivation of six gram-negative bacteria (Escherichia coli, Pseudomonas fluorescens, Salmonella enterica serovar Typhimurium, Salmonella enteritidis, Shigella sonnei, and Shigella flexneri) by high hydrostatic pressure treatment in the presence of hen egg-white lysozyme, partially or completely denatured lysozyme, or a synthetic cationic peptide derived from either hen egg white or coliphage T4 lysozyme. None of these compounds had a bactericidal or bacteriostatic effect on any of the tested bacteria at atmospheric pressure. Under high pressure, all bacteria except both Salmonella species showed higher inactivation in the presence of 100 μg of lysozyme/ml than without this additive, indicating that pressure sensitized the bacteria to lysozyme. This extra inactivation by lysozyme was accompanied by the formation of spheroplasts. Complete knockout of the muramidase enzymatic activity of lysozyme by heat treatment fully eliminated its bactericidal effect under pressure, but partially denatured lysozyme was still active against some bacteria. Contrary to some recent reports, these results indicate that enzymatic activity is indispensable for the antimicrobial activity of lysozyme. However, partial heat denaturation extended the activity spectrum of lysozyme under pressure to serovar Typhimurium, suggesting enhanced uptake of partially denatured lysozyme through the serovar Typhimurium outer membrane. All test bacteria were sensitized by high pressure to a peptide corresponding to amino acid residues 96 to 116 of hen egg white, and all except E. coli and P. fluorescens were sensitized by high pressure to a peptide corresponding to amino acid residues 143 to 155 of T4 lysozyme. Since they are not enzymatically active, these peptides probably have a different mechanism of action than all lysozyme polypeptides.